Health‐related quality of life after laparoscopic and open surgery for rectal cancer in a randomized trial. Issue 7 (3rd May 2013) - Andersson, J.; Angenete, E.; Gellerstedt, M.; Angerås, U.; Jess, P.; Rosenberg, J.; Fürst, A.; Bonjer, J.; Haglind, E.
<x xml:space="preserve">Abstract</x> Background Previous studies comparing laparoscopic and open surgical techniques have reported improved health‐related quality of life (HRQL). This analysis compared HRQL 12 months after laparoscopic versus open surgery for rectal cancer in a subset of a randomized trial. Methods The setting was a multicentre randomized trial (COLOR II) comparing laparoscopic and open surgery for rectal cancer. Involvement in the HRQL study of COLOR II was optional. Patients completed the European Organization for Research and Treatment of Cancer (EORTC) QLQ‐C30 and QLQ‐CR38, and EuroQol – 5D (EQ‐5D™) before surgery, and 4 weeks, 6, 12 and 24 months after operation. Analysis was done according to the manual for each instrument. Results Of 617 patients in hospitals participating in the HRQL study of COLOR II, 385 were included. The HRQL deteriorated to moderate/severe degrees after surgery, gradually returning to preoperative values over time. Changes in EORTC QLQ‐C30 and QLQ‐CR38, and EQ‐5D™ were not significantly different between the groups regarding global health score or any of the dimensions or symptoms at 4 weeks, 6 or 12 months after surgery. Conclusion In contrast to previous studies in patients with colonic cancer, HRQL after rectal cancer surgery was not affected by surgical approach. Registration number: NCT0029779 (http://www.clinicaltrials.gov).